2018
DOI: 10.1172/jci94003
|View full text |Cite
|
Sign up to set email alerts
|

A review of current theories and treatments for phantom limb pain

Abstract: Following amputation, most amputees still report feeling the missing limb and often describe these feelings as excruciatingly painful. Phantom limb sensations (PLS) are useful while controlling a prosthesis; however, phantom limb pain (PLP) is a debilitating condition that drastically hinders quality of life. Although such experiences have been reported since the early 16th century, the etiology remains unknown. Debate continues regarding the roles of the central and peripheral nervous systems. Currently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 89 publications
0
113
0
8
Order By: Relevance
“…TMS assessment of cortical reorganization provides insights into PLP underlying mechanisms. Understanding the mechanisms of central reorganization can be used to explain the potential pain modulation effects of neuromodulation techniques, such as non-invasive brain stimulations (Collins et al, 2018;Meeker et al, 2019). Regarding the previous studies showing the top-down motor cortex modulation of pain networks through thalamocortical connections (Garcia-Larrea et al, 1999;Miranda et al, 2006;Yoon et al, 2014), the motor cortex can be a potential treatment target to decrease PLP.…”
Section: The Intensity Of Pain Is Associated With the Level Of Reorgamentioning
confidence: 99%
“…TMS assessment of cortical reorganization provides insights into PLP underlying mechanisms. Understanding the mechanisms of central reorganization can be used to explain the potential pain modulation effects of neuromodulation techniques, such as non-invasive brain stimulations (Collins et al, 2018;Meeker et al, 2019). Regarding the previous studies showing the top-down motor cortex modulation of pain networks through thalamocortical connections (Garcia-Larrea et al, 1999;Miranda et al, 2006;Yoon et al, 2014), the motor cortex can be a potential treatment target to decrease PLP.…”
Section: The Intensity Of Pain Is Associated With the Level Of Reorgamentioning
confidence: 99%
“…The authors concluded that cortical disinhibition seems to be disassociated with mirror pain. However, acquired mirror pain likely has different mechanisms ( 2 ) compared to PLP.…”
Section: Discussionmentioning
confidence: 99%
“…After amputation, cortex's afferent inputs from amputated limb are interrupted, resulting in decreased cortical excitation, affecting local inhibitory drive (1). Decreased cortical inhibition seems to be maladaptive and can be related with other dysfunctional behaviors, like PLP (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, commonly used treatments for PN and PLP are currently diverse, unreliable, and without standardization. 19 , 37 39 Although respondents were familiar with most treatments in our comprehensive list, clear, distinct patterns of preferred management strategies for PN and PLP emerged. Injection, topical and surgical treatments were more commonly used for PN.…”
Section: Discussionmentioning
confidence: 99%